Which outcomes have been measured in hand eczema trials?: a systematic review - Rönsch, Henriette; Matterne, Uwe; Ofenloch, Robert; Weisshaar, Elke (Contact dermatitis, 2019)
The considerable heterogeneity of outcomes and measurement instruments in hand eczema trials substantially limits the evidence synthesis concerning therapeutic and preventive interventions. Therefore, the Hand Eczema Core Outcome Set (HECOS) initiative is developing a core outcome set for future trials. The first objective was to identify outcomes that were measured in previous trials, to group them in domains, and to identify their measurement instruments. We conducted a systematic review of controlled and randomized controlled hand eczema trials published since 2000. Sixty-one eligible studies were identified. Each assessed one or more of 47 outcomes in the “skin” domain. Eighteen trials (30%) additionally focused on preventive behaviour in risk occupations. Quality of life was measured in 13 studies (21%). Thirty-two distinct named instruments were applied, but 223 measurements (62%) were conducted with unnamed instruments. Only 32 studies (52%) defined a primary outcome. Twenty-nine trials (48%) provided some information on adverse events, but none gave any references concerning relevant methods. Our review confirms the need to harmonize outcome measurements in hand eczema trials. The findings form the basis for a consensus process to generate a core outcome set to improve the explanatory power and comparability of future hand eczema studies.